2014
DOI: 10.1111/gcb.12416
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for key enzymatic controls on metabolism of Arctic river organic matter

Abstract: Permafrost thaw in the Arctic driven by climate change is mobilizing ancient terrigenous organic carbon (OC) into fluvial networks. Understanding the controls on metabolism of this OC is imperative for assessing its role with respect to climate feedbacks. In this study, we examined the effect of inorganic nutrient supply and dissolved organic matter (DOM) composition on aquatic extracellular enzyme activities (EEAs) in waters draining the Kolyma River Basin (Siberia), including permafrost-derived OC. Reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
94
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 55 publications
(82 reference statements)
14
94
2
Order By: Relevance
“…Furthermore, selective processing and loss of permafrostderived DOM has been shown to occur via microbial metabolism throughout the Kolyma River basin, as waters move downstream through the fluvial network (Mann et al, 2014Spencer et al, 2015). Here, we complement these previous studies by providing extensive spatial characterization of DOM along a flow-path continuum from soil pore waters to the Kolyma River mainstem during midsummer (July) baseflow.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Furthermore, selective processing and loss of permafrostderived DOM has been shown to occur via microbial metabolism throughout the Kolyma River basin, as waters move downstream through the fluvial network (Mann et al, 2014Spencer et al, 2015). Here, we complement these previous studies by providing extensive spatial characterization of DOM along a flow-path continuum from soil pore waters to the Kolyma River mainstem during midsummer (July) baseflow.…”
Section: Introductionmentioning
confidence: 68%
“…The higher overall amounts of bioavailable DOC we measured in soil pore waters may reflect a highly bioreactive permafrost or aged surface soil derived fraction of the bulk DOC pool (e.g., Vonk et al, 2013;Mann et al, 2014). Further downstream in larger tributary and Kolyma mainstem waters, it has been shown that lower total amounts of bioavailable DOC is supported almost entirely from predominantly modern radiocarbon aged surface soils and vegetation sources .…”
Section: Biogeosciencesmentioning
confidence: 75%
See 2 more Smart Citations
“…4412 B. N. Deshpande et al: Bacterial production in thermokarst lakes 2009). The availability of organic substrates from these vast permafrost peatland environments to bacterial communities in aquatic ecosystems is likely to be influenced by a variety of factors, including the soil biogeochemical composition, particle and molecular size, and potentially other environmental factors, such as nutrient concentrations and temperature (Mann et al, 2014;Lapierre et al, 2013). Lakes in the boreal zone with flat catchments dominated by forest and peatland areas are strongly heterotrophic systems that have high rates of bacterial production (e.g., Kankaala et al, 2006), but less is known about the bacterial characteristics of peatland lakes further northwards, in permafrost regions.…”
mentioning
confidence: 99%